CXCL12-regulated miR-370–3p functions as a tumor suppressor gene by targeting HMGA2 in nonfunctional pituitary adenomas. (15th May 2019) - Cai, Feng; Dai, Congxin; Chen, Shasha; Wu, Qun; Liu, Xiaohai; Hong, Yuan; Wang, Zhen; Li, Li; Yan, Wei; Wang, Renzhi; Zhang, Jianmin
Abstract: Silencing of noncoding genes within the imprinted DLK1-MEG3 locus is exclusive to human nonfunctional pituitary adenomas (NFPAs), but the exact mechanism is still unclear. This study was designed to demonstrate the impact of CXCL12 on the expression of miRNAs within this locus and phenotypic alterations of NFPAs. Human NFPA samples were collected for screening differentially expressed miRNAs by CXCL12. Target mRNAs of the miRNAs were predicted and verified in vitro. Tumor phenotypic alterations were also tested. Another 51 NFPA samples were enrolled to examine the correlation and clinical features. The expression of miR-370 was decreased by CXCL12 treatment in NFPAs. miR-370–3p was predicted and verified to target HMGA2 as a tumor suppressor gene. Overexpression of HMGA2 inhibited its antitumor function. miR-370–3p was downregulated and HMGA2 was upregulated significantly in High grade NFPAs. In conclusion, the CXCL12/miR-370–3p/HMGA2 signaling pathway is involved in tumor growth and invasiveness of NFPAs. Highlights: CXCL12 treatment inhibits miR-370 expression in human NFPAs in vitro. miR-370–3p suppresses proliferation and invasion of NFPAs via targeting HMGA2. miR-370–3p/HMGA2 regulate Ki-67, XIAP, MMP2/9, Snail expression in vitro. miR-370–3p expression is reduced significantly in High grade NFPAs. The elevated HMGA2 level in High grade NFPAs has a trend to be negatively correlated with miR-370–3p level.